Egyptian Tales, Translated from the Papyri: First series, IVth to XIIth dynasty - Petrie, W. M. Flinders (William Matthew Flinders), 1853-1942 (Salt Lake City, UT : Project Gutenberg, 2005)
"Egyptian Tales, Translated from the Papyri: First Series, IVth to XIIth Dynasty" by W. M. Flinders Petrie is a collection of ancient Egyptian stories written during the late 19th century. This work aims to present some of the oldest known tales in the world to English readers, with a focus on their cultural and historical significance. The stories encompass various themes such as magic, adventure, and social intricacies, showcasing the literary richness of ancient Egyptian civilization. The opening of this collection introduces the context of the tales and sets the stage for the narrative style that follows. It begins with King Khufu calling upon his sons and counselors to recount stories that highlight the deeds of magicians from the past. Khafra, one of his royal sons, initiates this storytelling with a tale about enchantment involving a crocodile and a page, eventually leading to themes of loyalty, deception, and punishment. This blend of fantastical elements with moral lessons establishes a glimpse into the social norms and beliefs of ancient Egypt, while also promising further enchanting tales that explore human and supernatural interactions. (This is an automatically generated summary.)
Release date is 2005-01-01
Produced by Eric Eldred and David Widger
Keywords: Egyptian literature -- Translations into English